Epidemiological Study of Small Ruminant Diseases in Selected Districts of Kaffa and Bench- Maji Zone, Southern Nations Nationalities and Peoples Regional State (SNNPRs), Ethiopia (Global Journal of Medical Research, 2017)
An epidemiological survey of small ruminant disease was conducted in Boka-Shuta, Konda-Zuriya and Debre-Work kebelles of Kaffa and Bench-Maji zone, Southern Nations, Nationalities and people's regional state (SNNPRs), Ethiopia from July 2012 to June 2013. The objective of the study was to assess diseases of small ruminants affecting production and productivity; their occurrence and distribution; and associated risk factors. For these, Semi structured questioner format was prepared and survey was conducted. The result revealed that, 90.6%, 76.0% and 65.6% of interviewed farmers describe the multi-factorial causes of respiratory diseases; systemic diseases; and Gastro-intestinal parasite respectively were the most prevalent diseases irrespective of agro-ecology difference. The type of disease conditions documented in each agro-ecology had differences. Bloating (accumulation of excess amount of fluid in their abdominal cavity and blood tinged internal organs observed when slaughtered) followed by head circling in Boka-Shuta (highland); gastro intestinal parasite and head circling in Debre-Work (midland); and bottle jaw and orf in Konda-Zuriya (lowland) were the most prevalent and had serious problems in small ruminant production and productivity.
Keywords: agro-ecology; diseases; epidemiology; production; small ruminant; susceptible